Legal discourse and legal narratives : adversarial versus inquisitorial models - Ainsworth, Janet (Language and Law / Linguagem e Direito, 2017)
Global legal systems can be divided into those that are essentially adversarial in nature and those that are essentially inquisitorial. In recent decades, many countries that traditionally used inquisitorial processes have adopted more adversarial models of evidence presentation in trials, giving lawyers a more prominent role and judges a less prominent one. As a result, control over the creation of legal narratives in trials has passed from judges to the litigants, through their proxies, the lawyers. Adversarial trial evidence is developed primarily from oral question-and-answer sequences between the lawyers and witnesses, whereas in inquisitorial trials, judges construct legal trial narratives mainly through written witness statements. The linguistic characteristics of adversarial evidence presentation have implications for public perception of procedural justice and the legitimacy of law. Social psychology studies predict that the procedural justice consequences of this change in trial practice will be positive in some aspects, but potentially negative in others.